Is red distribution width a valid tool to predict impaired iron transport in heart failure? - Campodonico, Jeness; Carulli, Ermes; Doni, Francesco; Russo, Gerardo Lo; Junod, Daniele; Gaudenzi Asinelli, Margherita; Bonomi, Alice; De Martino, Fabiana; Vignati, Carlo; Pezzuto, Beatrice; Agostoni, Piergiuseppe (Frontiers in Cardiovascular Medicine, 2023)
Background Impaired iron transport (IIT) is a form of iron deficiency (ID) defined as transferrin saturation (TSAT) < 20% irrespective of serum ferritin levels. It is frequently observed in heart failure (HF) where it negatively affects prognosis irrespective of anaemia. Objectives In this retrospective study we searched for a surrogate biomarker of IIT. Methods We tested the predictive power of red distribution width (RDW), mean corpuscular volume (MCV) and mean corpuscular haemoglobin concentration (MCHC) to detect IIT in 797 non-anaemic HF patients. Results At ROC analysis, RDW provided the best AUC (0.6928). An RDW cut-off value of 14.2% identified patients with IIT, with positive and negative predictive values of 48 and 80%, respectively. Comparison between the true and false negative groups showed that estimated glomerular filtration rate (eGFR) was significantly higher (p = 0.0092) in the true negative vs. false negative group. Therefore, we divided the study population according to eGFR value: 109 patients with eGFR ≥ 90 ml/min/1.73 m2, 318 patients with eGFR 60–89 ml/min/1.73 m2, 308 patients with eGFR 30–59 ml/min/1.73 m2 and 62 patients with eGFR < 30 ml/min/1.73 m2. In the first group, positive and negative predictive values were 48 and 81% respectively, 51 and 85% in the second group, 48 and 73% in the third group and 43 and 67% in the fourth group. Conclusion RDW may be seen as a reliable marker to exclude IIT in non-anaemic HF patients with eGFR ≥60 ml/min/1.73 m2.